Pelatihan Simple Emergency Management untuk Peningkatan Kapasitas Kader LLHPB ‘Aisyiyah Gamping - Muhammad Thesa Ghozali; Vella Lailli Damarwati; Salmah Orbayinah; Hari Widada; Nanang Kurniawan; Riyanti Raf’al Dini; Ghaida Rahmani Putri Abidin (Jurnal Medika: Medika, 2025)
The purpose of this community service is to improve the capacity of LLHPB PCA ‘Aisyiyah Gamping cadres in managing emergency drug management through Simple Emergency Management training, as well as building an independent and sustainable community emergency response system. This community service activity uses the Asset-Based Community Development (ABCD) approach which emphasizes strengthening the internal potential of the community, such as LLHPB cadres, local pharmacists, and networks with the Drug Assistance Team (TBO) Sedative of the Pharmacy Study Program, Muhammadiyah University of Yogyakarta and BPBD. The implementation stages include asset identification (discover), formulation of a shared vision (dream), action planning (design), to implementation and sustainability (destiny) through participatory and contextual Simple Emergency Management training. As a result, a Drug Alert Team was formed and there was a significant increase in the understanding and skills of the cadres, demonstrating the effectiveness of the ABCD approach in building community independence in dealing with emergency situations. The results of the activity showed an increase in community capacity in managing emergency drugs. The Simple Emergency Management training succeeded in improving participants' understanding based on the results of the pre-test and post-test. Local cadres play an active role as facilitators, and the training process is designed in a participatory manner according to the community's potential. This program not only improves technical knowledge, but also strengthens the independence and sense of community ownership in dealing with emergency situations.